The protein and energy requirements of the east african boran cattle - Karue, C.N. (1977)
During a study on voluntary intake of dry matter (DMI) with 108 Zebu steers, lives weight gain data were collected over an 84-day period. The steers in Experiment 1 were approximately 2.5 years old, with an average weight of 271 kg. They were fed poor quality hay (7 percent CP, 80 percent CWC) ad libitum, supplemented with restricted amounts of nine concentrates providing cassava and molasses for energy and urea for nitrogen (N). Data were collected fortnightly for the DMI and for three consecutive days 3 to 5, 45 to 47 and 80 to 82 of the 84-day feeding period, for the body weight. The digestibility data were collected in experiment 2 with 40 Zebu steers of approximately 2.5 years of age, with an average weight of 195 kg. They were fed similar hay supplement with restricted amounts of concentrates as in Experiment 1 and total faeces and urine collected on days 21 and 26 inclusive, during a 28-day metabolism trial. Protein requirement for maintenance was estimated as the protein required to replace endogenous urinary nitrogen (EUN) excretion, from the equation, RN=0.30 DN + 0.62 DE-105±17.7 (p